The perception of patients undergoing gynecological brachytherapy treatment (Research, Society and Development, 2021)
Introduction: Brachytherapy is a type of radiotherapy in which the radioactive source is placed within or near the area to be treated. The insertion may be temporary or permanent. One of the most important characteristics of brachytherapy is that the radiation generated by the source affects only areas very close to the site that will be treated, thus protecting healthy tissues. Objective: To know the meaning of brachytherapy and the painful perception of women with gynecological cancer submitted to this therapy in a Reference Unit in a city in the interior of Maranhão. Methodology: This is an exploratory descriptive research, with a quantitative approach. Results: During the preparation procedures for brachytherapy, during and after the withdrawal of the closure of the procedure, it was noticed that the findings in relation to pain perception remained the same as burning, burning colic and constant pain. Even with its significant benefits, this treatment also presents adverse effects that may be irreversible if it is not properly maintained, so it is extremely important to understand the weaknesses and fears presented by patients regarding the disease and treatment, helping to adapt to this new condition and answer doubts, more efficient and appropriate assistance. Conclusions: Finally, it is concluded that it is necessary to expand the investigation of the sociodemographic and clinical profile through a quantitative study, only in this way will it be possible to establish a broader overview of the women assisted in a Reference Unit.